Wind direction sensor based on thermal anemometer for olfactory mobile robot - Helmy Widyantara; Muhammad Rivai; Djoko Purwanto (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A wind direction sensor has been implemented for many applications, such as navigation, weather, and air pollution monitoring. In an odor tracking system, the wind plays the important role to carry gas from its source. Therefore, the precise, low-cost, and effective wind direction sensor is required to trace the gas source. In this study, a new design of wind direction sensor has been developed using thermal anemometer principle with the main component of the positive temperature coefficient thermistor. Three anemometers each of which has different directions are used as inputs for the neural network to determine the direction of the wind automatically.The experimental results show that the wind sensor system is able to detect twelve wind directions. A mobile robot equipped with this sensor system can navigate to a wind source in the open air with a success rate of 80%.This system is expected to increase the success rate of the mobile robot in searching for dangerous leaking gas in the open air.